Autoimmune-Associated Seizures. Issue 2 (April 2022) - Gillinder, Lisa; Britton, Jeffrey
ABSTRACT: PURPOSE OF REVIEW: This article focuses on the seizure manifestations and presentations of autoimmune-associated epilepsy and acute symptomatic seizures in autoimmune encephalitis. It discusses the specificity of the various central nervous system autoantibodies and clarifies when their presence can be considered indicative of an immune etiology. Finally, current recommendations regarding patient selection for autoimmune antibody evaluation are reviewed, and an approach to immunotherapy is provided. RECENT FINDINGS: Although autoimmune seizures are caused by a heterogeneous group of autoantibodies, key features reported in the literature should alert clinicians to the possible diagnosis. In particular, seizure characteristics including frequency, timing, duration, and symptomatology can provide vital clues to help differentiate autoimmune-associated seizures from other causes of epilepsy. Diagnostic certainty also requires an understanding and integration of the spectrum of clinical and paraclinical presentations, and several scoring systems have been developed that may be useful to aid the identification of autoimmune seizures. SUMMARY: Seizures due to autoimmune etiology are increasingly encountered in clinical practice. It is critical that clinicians recognize immune seizure etiologies early in their course given they are often responsive to immunotherapy but are usually resistant to antiseizure medications. Currently, however, it is unfortunately not uncommon for autoimmune-associated seizure disorders to remain undiagnosed, resulting in missed opportunities to administer effective therapies. Efforts to better understand autoimmune seizure manifestations and treatment strategies are ongoing.